The challenges towards the emergence of an African higher design education: case study of a French design diploma relocated to Benin - (:unkn) unknown (My University, 2023)
In October 2019, Francophone Africa's first graduating design school opened its doors in Cotonou, Benin. A French private design school, chosen by a Beninese government agency, carried the project and recruited me to create and run the school. For nearly three years, as an observer-participant, I fulfilled the mission of delocalizing the French diploma to Benin, which acts as a normative instrument. Although the project responds to a market, this approach produces a double effect: the importation of a French pedagogical culture, but also of a French design culture in Benin. As design education in French-speaking Africa emerges, and as international design research simultaneously focuses on decolonising design and design education through a pluriversal lens, this case study aims to analyse the issues at stake in this model of design education in Benin, which is already paving the way for a multiplication in the coming years.
Keywords: African Research